2019
DOI: 10.1016/j.apenergy.2019.04.105
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution assessment of solar energy resources over the Arabian Peninsula

Abstract: This study presents a high-resolution spatial and temporal assessment of the solar energy resources over the Arabian Peninsula (AP) from 38 years reanalysis data generated using an assimilative Weather Research and Forecasting Solar model. The simulations are performed based on two, two-way nested domains with 15 km and 5 km resolutions using the European Centre for Medium-Range Weather Forecasts as initial and boundary conditions and assimilating most of available observations in the region. Simulated solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 84 publications
1
55
0
Order By: Relevance
“…Further details on the experimental design and methodology as well as the comparative advantages of such a regional analysis compared to other global products are provided by Viswanadhapalli et al (2016). The regional reanalysis has been also used and validated in various studies and applications (Dasari et al, 2017, 2019; Langodan et al, 2014, 2015, 2016, 2017; Viswanadhapalli et al, 2016; Zhan et al, 2016).…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…Further details on the experimental design and methodology as well as the comparative advantages of such a regional analysis compared to other global products are provided by Viswanadhapalli et al (2016). The regional reanalysis has been also used and validated in various studies and applications (Dasari et al, 2017, 2019; Langodan et al, 2014, 2015, 2016, 2017; Viswanadhapalli et al, 2016; Zhan et al, 2016).…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…A 38‐year (1980–2018) high‐resolution reanalysis (Viswanadhapalli et al ., ; Langodan et al ., , ; Bindu et al ., ; Dasari et al ., ; Viswandhapalli et al ., 2019), generated using the Weather and Research Forecasting (WRF) model (Skamarock et al ., ) and ERA‐Interim (ERA‐I) reanalysis (Dee et al ., ), was used to study the prevailing anomalous atmospheric circulation patterns over Kerala in August 2018. Generally, global reanalyses provide acts as a good source of information for studying severe weather conditions.…”
Section: Methodsmentioning
confidence: 99%
“…These are located at Mattanur (11.92 N,75.57 E),Thamarassery (11.415 N,75.940 E), Pookot (11.542 N,76.027 E), Vellanikkara (10.545 N, 76.2740 E), Kudlu Agro (12.5299 N, 74.9881 E), Mankara Agro (10.7918 N, 76.4997 E), Vellanikkara (10.5452 N, 76.2740 E), Neeleswaram (11.347 N, 75.972 E), Erimayur (10.659 N, 76.572 E), andMeenangadi (11.6596 N, 76.1726 E). We also used the satellite-rain gauge merged rainfall estimates of IMD (Mitra et al, 2009(Mitra et al, , 2013 to analyze the spatial characteristics of extremely heavy rainfall (shown in A 38-year (1980-2018) high-resolution reanalysis (Viswanadhapalli et al, 2017;Langodan et al, 2017aLangodan et al, , 2017bBindu et al, 2018;Dasari et al, 2019;Viswandhapalli et al, 2019), generated using the Weather and Research Forecasting (WRF) model (Skamarock et al, 2008) and ERA-Interim (ERA-I) reanalysis (Dee et al, 2011), was used to study the prevailing anomalous atmospheric circulation patterns over Kerala in August 2018. Generally, global reanalyses provide acts as a good source of information for studying severe weather conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the solar intensity is higher than the required critical values. Extended research was conducted by Dasari et al [25] to evaluate the solar energy resources over the Arabian Peninsula, including Saudi Arabia, across 38 years . The data were collected from 46 in-situ radiometer stations to analyse the GHI, DNI, and DHI.…”
Section: Solar Energymentioning
confidence: 99%